(untitled) (Journal of Atomic and Molecular Sciences, 2022)
The equilibrium geometries of Si_2N have been calculated using different quantum chemistry calculation methods. Through a large number of test and research, the method QCISD/6-31G(2d,2p) is the most suitable for the calculation of Si_2N by comparing the experimental equilibrium structure and harmonic frequency data. The force constants have also been calculated. Based on the general principles of microscopic reversibility, the dissociation limits has been deduced. The analytical potential energy function of Si_2N has been obtained based on the many-body expansion theory. The potential surface graphs have been presented. It's found that there is a minimum value of 4.725eV at stable structure of the potential surface and a potential well of 1.7eV correspond to the linear asymmetric structures(^2Π). And the reaction of SiN+Si → SiNSi based on the potential energy surface is discussed briefly, which is successfully used for describing molecular reaction dynamics.